Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What is the intersection of the following two subspaces and why?

$U \cap W$ with $U=\langle 2-e^{3x},4x+e^{3x}\rangle$ and $W=\langle 1,e^x, e^{3x}\rangle$. I thought too easily: $e^x$ can't be in the union, because nothing in $U$ can be written as $\lambda e^x$ and $x$ can't be in the union because it won't fit in $W$.

share|improve this question
    
Do you really mean union or do you mean sum, that is, the smallest subspace containing $U$ and $W$? –  lhf Jan 20 '12 at 13:01
1  
union? union of sub-spaces is not a sub-space unless one is contained in the other. Do you mean sum? Or intersection? –  Dennis Gulko Jan 20 '12 at 13:01
    
Sorry for that! I meant intersection ;). –  Kevin Jan 20 '12 at 13:08
    
Please use \langle and \rangle for the angle brackets in TeX. The symbols < and > not only look different, they also give different spacing because they are relation symbols. –  Harald Hanche-Olsen Jan 20 '12 at 13:24
    
Thanks, you are right. Looks now more it looks like in my book :). –  Kevin Jan 21 '12 at 8:04
add comment

3 Answers

up vote 1 down vote accepted

I would not call that union, but instead an intersection. Let's do it from the very definition : the intersection is made of the element of W which are also in U, i.e. those elements of the form $a + b e^x + c e^{3x}$ ($a,b,c\in\mathbb R$) such that there exists $u$ and $v$ (also real numbers) with $$a + b e^x + c e^{3x} = u(2-e^{3x}) + v (4x + e^{3x}) \qquad \forall x \in \mathbb R$$ Re-arrange this: $$a + b e^x + c e^{3x} = 2 u + 4 v x + (v - u) e^{3x} \qquad \forall x \in \mathbb R$$ For this to be satisfied, you need (because the functions which map $x$ to $1$, $x$, $e^{x}$ and $e^{3x}$ are all linearly independent): $$ \begin{cases} a = 2 u\\ b = 0\\ 4 v = 0\\ c = v - u \end{cases} $$ which is equivalent to $$ \begin{cases} a = - 2 c\\ b = 0\\ v = 0\\ u = -c \end{cases} $$ You thus need $(a,b,c) = (-2C, 0, C)$ for some real number $C$, and then indeed there exists $(u,v)$ (namely $(-C, 0)$) such that the system is satisfied. This means that the elements of the intersection are all the multiples of $-2 + e^{3x}$.

share|improve this answer
add comment

One possible way: since $U\not\subseteq W$ and $dim U=2$, $dimW=3$, you know that $dim(U\cap W)$ is either $0$ or $1$ (why?). You can see that $2-e^{3x}$ is an element of both $U$ and $W$ (why?), hence is an element of $U\cap W$. This implies that $U\cap W=\langle2-e^{3x}\rangle$ (how?).

share|improve this answer
add comment

Ah, found a proof myself :), is this correct?

Take $x \in U \cap W$. Since $x \in U$ it holds that $x = \lambda (2-e^{3x})+ \mu (4x + e^3x)$. $x \in W \Rightarrow x = \alpha \cdot 1 + \beta e^x + \gamma e^{3x}$. For any $\gamma, \mu, \alpha, \beta, \gamma$. Since $x = x$ we can subtract those two expressions which gives: $0=1 \cdot (2 \lambda - \alpha) + x(4 \mu) - e^x \cdot \beta + e^{3x} (\mu -\lambda - \gamma)$ and since $1, x, e^x$ and $e^{3x}$ are linear independent (I will not proof that), it follows that $\beta = 0, \mu = 0, 2 \lambda = \alpha, -\lambda=\gamma$. Now choose $\epsilon = \lambda$, then $\gamma = -\epsilon$ and $\alpha = 2 \epsilon$. Filling this in for $x$ gives $x = \epsilon (2 - e^{3x})$ and in the other equation: $x = 2\epsilon - \epsilon e^{3x} = \epsilon(2-e^{3x})$. And since $\lambda$ is a free variable, so is $\epsilon$, so $x \in U \cap W \Leftrightarrow x \in <2 - e^{3x}>$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.